Sustaining Employment and Wage Gains in Brazil : A Skills and Jobs Agenda - Silva, Joana (Washington, DC: World Bank, 2015)
In the past 15 years, employment, labor market participation, and wages have grown significantly in Brazil. Improved labor market outcomes have been the main drivers of reductions in poverty and inequality. But job creation is already slowing. Continued progress in employment and labor earnings will depend on the country’s ability to achieve a first critical goal: raising labor productivity. Continued improvements in the livelihoods of the poor will depend on the country’s ability to achieve a second critical goal: connecting the poor to better, more productive jobs.